Leveraging what on-line offers in evaluating course and instructors - David A Line (Academic Chairpersons Conference Proceedings, 2022)
At most institutions of higher education COVID-19 forced the delivery of courses on-line. This has required department chairs to re-think traditional, on-ground, faculty evaluative strategies. This session explores the benefits of applying readily available, on-line course methodologies and metrics to enhance chair support and evaluation of departmental faculty teaching efforts.
Keywords: On-line Evaluation Course Development Delivery